Brahmi legends on Umayyad Fulus: Interrogating local minting practices and numismatic transculturation in Gandhara (ca. 750 CE). Issue 1 (April 2019) - Ziad, Waleed
Abstract : This paper concerns a historically significant find of copper derivatives of Umayyad post-reform fulus from Gandhara, probably minted in the mid-eighth century under Turk Shahi sovereignty (c. 667–875). The coins share an unusual feature: two Brahmi aksharas on an Umayyad AE prototype, inversely oriented to a partially-corrupted Arabic legend. These base metal coins represent perhaps the only known caliphal imitative varieties issued by moneyers beyond the eastern limits of Umayyad and Abbasid sovereignty. They have the potential to inform our understanding of the complex relationship between political authority, confessional identity, and coin typology in late antiquity – particularly within early "Hindu"– "Muslim" contact zones. Moreover, they provide invaluable clues into the circulatory regimes of Umayyad coinage.